Dissociable fronto-striatal functional networks predict choice impulsivity - Wang, Qiang; Lv, Chenyu; He, Qinghua; Xue, Gui (Brain structure & function, 2020)
Fronto-striatal structural connectivity is associated with choice impulsivity. Yet, to date, whether distinct fronto-striatal functional coupling associates with impulsive choices are largely unknown. Using seed-based resting-state functional MRI (rsfMRI) combined with multivariate pattern analysis (MVPA), the present study aimed to explore the predictions of dissociable frontal–striatal functional connectivity on choice impulsivity in a relatively large sample ( N = 429). Adaptive delay-discounting task was utilized to assess choice impulsivity and the striatum was further divided into three subregions including the nucleus accumbens (NAcc), caudate, and putamen. Results revealed that both the functional coupling between the NAcc and the limbic/dorsolateral prefrontal cortex, and between the caudate and the dorsal prefrontal cortex, including the dorsomedial prefrontal cortex (DMPFC), successfully predicted the delay-discounting rate. However, such pattern was not observed in the putamen-prefrontal functional connectivity. These findings suggest fronto-striatal-dependent neural mechanisms of choice impulsivity and further provide a better understanding of the contributions of striatum subregions and their functional connectivities with different areas of prefrontal cortex upon inter-temporal choice.